"المرايا" أو تشظي الذات - زروق، محمد (التأويل و تحليل الخطاب : مجلة دولية محكمة نصف سنوية., 2024)
This research aims to illustrate two things: firstly, the selection of a novel that is different in its structure and the delineation of its features, and secondly, to test the study of characters from a narrative perspective and how it connects with the realm of narrative discourse production. therefore, in the novel “al-Maraya” Naguib Mahfouz chose a different structure. the author did not construct novel on the conventional narrative structure, where events evolve, complicate, and resolve. but he chose the characters to be his focus point. in other words, the characters were the axes from which the narrator began his narration. the novel was actually mirrors that reflected the characters on the one hand and the narrator on the other one. indeed, the novel serves as mirrors reflecting images of characters selected by the narrator to be the subject of the story, thus reflecting the narrator's own self through their stories. therefore, in the present study, our approach involved analyzing various aspects of the novel to illustrate its characteristics. يهدف هذا البحث إلى بيان أمرين، الأول انتقاء رواية مختلفة في بنائها وتحديد معالمها، والثاني اختبار دراسة الشخصيات من وجهة نظر سردية مع وصل ذلك بمقام إنتاج الخطاب الروائي. لقد أقيمت رواية المرايا لنجيب محفوظ على طريقة في الرواية مختلفة، فالكاتب لم يبنها على معهود السرد الروائي، من بناء الحدث ينمو ويتعقد وينفرج، ولم يكن الحدث هو قوام الرواية، بل نهج إلى اعتماد الشخصية منطلقا للحكاية، فبنى روايته على شخصيات هي محور الحكاية، هي سير للشخصيات، تبدو في الظاهر متفرقة، غير أنها في الباطن متصلة بسبب من الأسباب، ولعل أهم رابط يصل متفرق الشخصيات هو الراوي الذي تتوزع سيرته وحكايته على هذا التوزع للشخصيات. الرواية فعلا هي مرايا تعكس صور شخصيات رشحها الراوي لتكون موضوع حكاية، ولتنعكس عليها الذات الراوية فتبدي حكايتها من خلال حكاياتها. ولذلك كانت هذه الرواية محور دراستنا دراسة خطابية لا تهمل الواقع الذي فيه تكونت الرواية، فكان انصرافنا إلى دراسة محاور منها حاولنا بيان خصائص هذه الرواية. وقد قطعت من البحث شوطا في جمع هذه الشخصيات في حقول دلالية تحركت فيها ونشأت، مثل الإدارة أو زمن الطفولة أو الدراسة، وهي دوائر تجمعت فيها هذه الشخصيات وتواصلت بعلاقات تشدها، وقد انتهيت إلى أن الرواية تفاعلت مع واقع مثلته الشخصيات المرشحة للرواية، وأحسنت تصويره وتمثيله.